The influence of interpersonal motivation on polish consumers’ online brand-related activity - Brzozowska-Woś, Magdalena; Schivinski, Bruno (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2019)
The development of social media has a substantial impact on the surge of social engagement of Internet users. It is particularly prominent in the domain of content creation and content sharing. Such communication may contain various references to different products brands and companies. Internet users may refer to them explicitly or brands may be present in the background only. Therefore, it is pivotal for managers and researchers to isolate the factors that may trigger consumers’ brand-related engagement in the Internet. The objective of the research was to determine whether the susceptibility to interpersonal influence (both informational and normative) stimulates the three types of group behavior associated with consumer brand-related activity in the social media. The dedicated online survey was completed by 1,025 Polish consumers and analyzed using structural equation modeling (SEM). The results demonstrate that the factors of informational social influence – irrespective of its type – directly influence the consumers’ online engagement with brands controlled for age, gender, social media and brand usage. Regardless of whether the brand communication is initiated by some organization or by the consumers themselves, an eagerness to share the content perceived as valuable on social media plays a prominent role
Argumenta Oeconomica, 2019, Nr 2 (43), s. 213-231
Keywords: consumers online brand-related activities; COBRAs; susceptibility to interpersonal influence; Polish internet users